2006
DOI: 10.1007/bf03194602
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA mutations in human neoplasia

Abstract: Many models of tumour formation have been put forth so far. In general they involve mutations in at least three elements within the cell: oncogenes, tumour suppressors and regulators of telomere replication. Recently numerous mutations in mitochondria have been found in many tumours, whereas they were absent in normal tissues from the same individual. The presence of mutations, of course, does not prove that they play a causative role in development of neoplastic lesions and progression; however, the key role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
81
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 67 publications
1
81
0
2
Order By: Relevance
“…Furthermore, we and others have shown that mtDNA deletions can be induced in cultured human skin cells by sublethal repetitive doses of UVA (Berneburg et al, 1999;Krishnan et al, 2004). In agreement with observations of mtDNA damage in other tumours (Birch-Machin, 2006;Czarnecka et al, 2006;Parr et al, 2006) we have previously identified somatic mtDNA changes in human skin as a result of the first detailed study of mtDNA damage in NMSC (Durham et al, 2002). Importantly, as a result of this study, we identified a 3895 bp mtDNA deletion which occurred more frequently in usually sun-exposed skin as opposed to occasionally sun-exposed skin Krishnan et al, 2004).…”
supporting
confidence: 87%
“…Furthermore, we and others have shown that mtDNA deletions can be induced in cultured human skin cells by sublethal repetitive doses of UVA (Berneburg et al, 1999;Krishnan et al, 2004). In agreement with observations of mtDNA damage in other tumours (Birch-Machin, 2006;Czarnecka et al, 2006;Parr et al, 2006) we have previously identified somatic mtDNA changes in human skin as a result of the first detailed study of mtDNA damage in NMSC (Durham et al, 2002). Importantly, as a result of this study, we identified a 3895 bp mtDNA deletion which occurred more frequently in usually sun-exposed skin as opposed to occasionally sun-exposed skin Krishnan et al, 2004).…”
supporting
confidence: 87%
“…In addition, the missense mutation G5460A affecting the ND2 was reported in pathologically proven Parkinson and Alzheimer's diseases (28). Therefore, it cannot be excluded that mtDNA polymorphisms may result in disturbed protein synthesis, synthesis rate or finally in changed protein structure and therefore influence mitochondrial and cell physiology with the consequence of cancer development susceptibility (3)(4)(5)8,29).…”
Section: Amino Acid Change Gene -------------------------------------mentioning
confidence: 99%
“…This discovery has opened a new field of research currently referred to as 'mitochondrial medicine' and 'mitochondrial oncology'. Multiple reports have found an association between somatic mtDNA mutations and cancer development, progression or metastasis and inherited mtDNA polymorphisms have been indicated as contributing factors in cancer development (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of mitochondrial DNA (mtDNA) sequences plays an important role in the studies on population genetics and in medicine, including veterinary medicine (7,11,12,(27)(28)(29)32). Results published in the recent years have indicated the prevalence of mitochondrial DNA mutations in tumour cells, which suggests that they may be cancer-causing agents (7,11,12,28,29,32,34).…”
Section: Introductionmentioning
confidence: 99%
“…Results published in the recent years have indicated the prevalence of mitochondrial DNA mutations in tumour cells, which suggests that they may be cancer-causing agents (7,11,12,28,29,32,34). Up till now, there has been not stated whether the observed changes in mitochondrial DNA result from the development of tumour or are connected with the process of neoplastic transformation (7,11,12,28,29). GrzybowskaSzatkowska and Slaska (12) report the presence of homological changes in the sequence of mtDNA in breast cancer and some mitochondrial diseases, which indicates that mutations in mtDNA in breast cancer may affect the cell and cause its dysfunction, as in the case of mitochondrial diseases.…”
Section: Introductionmentioning
confidence: 99%